Uses of quantitative spatial analysis and epidemiological simulation modeling for assessing control strategies for foot-and-mouth disease - Premashthira, Sith, author; Salman, Mo, advisor; Hill, Ashley, committee member; Reich, Robin, committee member; Wagner, Bruce, committee member (Colorado State University. Libraries, 2012)
This study addressed issues related to a hypothetical outbreak of foot-and-mouth disease (FMD) comparing a limited control measure to additional control strategies where there were limited control strategies within FMD virus free area. The central United States was selected as the study area, and the spatial pattern of FMD and its determinants were observed after FMD was introduced into the center of the area. The research reported the magnitude of the outbreaks in different scenarios having different control strategies. The first four chapters in this dissertation cover the sequence of research methods, and the final chapter includes the results and discussion. Chapter 1 reviews aspects of epidemiology of FMD, epidemiological simulation modeling, and spatial analysis with the focus on FMD in terms of disease control. The review stimulated some ideas to generate parameters for the FMD simulation modeling that was done in Chapter 2. Chapter 2 explains the process for generating parameters for a hypothetical outbreak of FMD in the central Unites States. The process included gathering location study premises in the study area from many sources and a simulator. The disease stage and transmission parameters of FMD were estimated from reviews and statistical analyses of data distribution, adjusted for study premises size. The sensitivity analysis of important parameters was analyzed by comparing disease spread for various values of the input parameters. Chapter 3 examines the practical plans in place for FMD control and eradication. The baseline scenario was set up from the base parameters from Chapter 2 and included some limited control strategies. The additional five strategies included additional intensive disease control measures such as restricted animal movement, additional animal destruction, or ring vaccination. The baseline and extra five scenarios were simulated in a simulator and their magnitude was observed, including epidemic duration and estimated number of destroyed and/or vaccinated animals. Chapter 4 identifies the simulated outbreak region and its spatial determinants in the baseline scenario. The density estimation of affected areas was determined and illustrated by maps. Additional quantitative spatial methods such as spatial continuity, autocorrelation, and autoregressive model were analyzed to explain spatial trends and factors related to the affected areas. Chapter 5 concludes the important findings of this research. The overall conclusion summarizes the results from the previous chapters. A hypothetical outbreak of FMD in a large study area such as the one in this research should identify the premises of livestock as the unit of interest. The spread of FMD in the area may be primarily caused by indirect contact rather than direct contact and airborne transmission. The change of parameters in the indirect contact rates was sensitive to the outcome of the simulation. All additional disease control strategies were better than the baseline scenario in terms of reducing the magnitude of the outbreak, but not in shortening the epidemic duration. For example, restricted animal movement was the best strategy to reduce magnitude of the outbreak, but it lengthened the epidemic duration. The kernel density estimation method demonstrated that the outbreak would spread throughout most of the study area. More affected premises in each county arose when higher numbers of livestock premises were in it and neighboring zones.
Keywords: control strategies; quantitative spatial analysis; foot-and-mouth disease; epidemiological simulation modeling